Analisis Determinan AS Dalam Penggunaan PMC Pada Perang Irak tahun 2003 - Dhiaulhaq, Yusuf; Windiani, Reni; Alfian, Muhammad Faizal (Journal of International Relations, 2022)
The phenomenon of the Iraq war in 2003 has given the impression of a major armed conflict between the United States and Iraq. What needs to be considered in this war is the involvement of private military companies (PMC) in the war. The US also used PMC services after the Iraq war ended where Iraq's internal conditions at that time were very unsafe and needed security guard. The United States uses PMC which provides various military services ranging from the distribution of weapons, exchange of war technology, provision of military forces, intelligence assistance, and so on. Therefore, this study seeks to explain the reasons and considerations when US decided to use PMC before and after the war by using the theory of determinants of foreign policy made by Alex Mintz. In this study, the authors collect data through books, journals, and websites related to the cases studied, namely the use of PMC by the US in Iraq. This study will explain the involvement of PMC in Iraq War, and the analysis from the determinants. The results obtained are several determinants of foreign policy that have a major influence on the US decision to use PMC in the conflict.